Javanese script digitalization and its utilization as learning media: an etnopedagogical approach - Iskandar, Didik; Hidayat, Soleh; Jamaludin, Ujang; Mukti Leksono, Suroso (International Journal of Mathematics and Sciences Education, 2023)
The purpose of this research is to analyze the digitization of the Javanese script and its use as a learning medium with an ethnopedagogical approach. Ethnopedagogy is a learning approach that integrates culture and local values ​​in the learning process. The research method used in this study is a literature review. The results of the research show that digitizing the Javanese script can help strengthen and maintain the existence of local culture, one of which is by learning the Javanese script. In addition, learning Javanese script can help develop students' creativity and abilities in art and literature. Utilization of technology and digital media can increase the effectiveness of learning Javanese script, such as making applications or computer programs that can make it easier for students to learn Javanese script. By utilizing digital media, students can learn Javanese script in a more interactive and interesting way. An ethnopedagogical approach to learning Javanese script can also help strengthen a sense of pride in local culture and maintain cultural heritage for future generations.